Access the diagnostic reliability and imaging evaluation of adnexal masses diagnosis ultrasonography, magnetic resonance imaging and computed tomography - Wadnere, Nitin; Ahuja, Ajit; Behl, Simran (International Journal of Research in Medical Sciences, 2021)
Background: Objective of the study was to evaluate role of diagnostic reliability of morphological characteristic of ovarian and adnexal masses to compare and correlated in sensitivity of ultrasonography, computed tomography, magnetic resonance imaging (USG with CT and MRI). Methods: This study was conducted in department of radiodiagnosis, Sri Aurobindo medical college and PG institute, Indore from August 2019 to September 2020. A total of 100 OPD patients of adnexal masses including both premenopausal and postmenopausal women. All 100 patients had undergone sonographic assessment and CA-125 levels were assessed; where 70 patients were correlated with CT and 30 patients were correlated with MRI with a standardized research protocol Results: A total of 100 patients included in the study. The mean age was 42.05±2.3. 68 (68%) patients were Premenopausal and 32 (32%) patients post-menopausal. 19 (19%) of patients had family history of ovarian carcinoma, whereas 81 (81%) of patients had negative family history of ovarian carcinoma. 32 (47%) patients in premenopausal group had increased Ca-125 levels, whereas 18 (56.2%) patients in postmenopausal had increased Ca-125 levels. Conclusions: MRI proved to be highly sensitive and accurate in differentiating benign and malignant lesions of adnexal masses which were indeterminate on ultrasonography examination. Thus, MRI can be considered as second most confirmatory tool followed by tissue diagnosis in women with indeterminate masses.